Understanding and Reducing Inconsistency in Seatbelt‐Use Decisions: Findings from a Cardinal Decision Issue Perspective. Issue 1 (19th May 2015) - Alattar, Laith; Yates, J. Frank; Eby, David W.; LeBlanc, David J.; Molnar, Lisa J.
Abstract : This article has two aims. The first is to present results that partly explain why some automobile drivers choose to use their seatbelts only part time, thereby exposing themselves to unnecessary risk. The second is to offer and illustrate the "cardinal decision issue perspective" (1) as a tool for guiding research and development efforts that focus on complex real‐life decision behaviors that can entail wide varieties of risk, including but not limited to inconsistent seatbelt use. Each of 24 young male participants drove an instrumented vehicle equipped to record continuously seatbelt use as well as other driving data. After all trips were finished, each participant completed an interview designed to reconstruct how he made randomly selected seatbelt‐use decisions under specified conditions. The interview also examined whether and how drivers established "decision policies" regarding seatbelt use. Such policies were good predictors of inconsistent seatbelt use. Drivers who had previously adopted policies calling for consistent seatbelt use were significantly more likely than others to actually drive belted. Meta‐decisions about seatbelt policy adoption appeared to rest on factors such as whether the driver had ever been asked to consider selecting a policy. Whether a driver made an ad hoc, on‐the‐spot seatbelt‐use decision was associated with a perceived need to make such a decision. Finally, participants with full‐time policies were especially likely to deploy their seatbelts by default, without recognizing the need to decide about belt use on a trip‐by‐trip basis. We end with recommendations for reducing inconsistencies in seatbelt use in actual practice.